Front Cover: Porous Organic Compounds – Small Pores on the Rise (Eur. J. Org. Chem. 43/2021). Issue 43 (11th November 2021) - Kunde, Tom; Pausch, Tobias; Schmidt, Bernd M.
Abstract : The Front Cover shows the diverse library of porous organic compounds, designed and synthesized by scientists working in the field featured in our review article. Porous organic cage compounds with their discrete nanocavities have emerged as a versatile functional‐materials platform and we highlight examples of porous organic cages with focus on how the intrinsic nanopore can be controlled and utilized, in addition to the synthesis and the gas sorption properties of smaller intrinsic pores of porous organic cage compounds, porous macrocycles and other related compounds. More information can be found in the Review by B. M. Schmidt et al .